Indonesian Student Movement Moral Force Doctrine in Social Change Under Jokowi’s Indonesia and Its Future - Adhipermana, Luthfi Diar (Talenta Publisher, 2022)
The development of Indonesian democracy is slowly regressing under Jokowi’s Administration, amidst that regression, two massive student movement occurred in 2019 and 2020. Despite the scale of the movement, those movement couldn’t maximize their success. This article attempts to answer two questions regarding that matter, first, why the student movement in Jokowi’s Administration couldn’t achieve success? Second, is the student movement still viable to do a social change? To answer those questions this article examined the moral force doctrine which constructed along with the student movement throughout the history. This article argue that the moral force doctrine needs to be abandoned because it made the student movement have an obscure position towards the establishment and limiting the student movement to build alliances with other political groups. Yet, the student movement still viable to do a social change in a time of crisis even it doesn’t change its doctrine.